Photocurable resin composition, adhesive sheet, and laminate manufacturing method
The photocurable resin composition, featuring a monofunctional (meth)acrylic monomer, multifunctional (meth)acrylic monomer, photopolymerization initiator, and styrene-derived thermoplastic resin, addresses the challenges of adhesion and creep resistance in existing adhesive compositions by providing a cured product with enhanced mechanical properties and surface hardening.
Patent Information
- Application Number
- JP2025013862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-01
- Filing Date
- 2025-01-30
- Publication Date
- 2025-04-17
AI Technical Summary
Existing photocurable adhesive compositions face challenges in achieving excellent adhesion and creep resistance, particularly when exposed to oxygen during curing, which can lead to incomplete hardening of the surface and reduced adhesion.
A photocurable resin composition is developed, comprising a monofunctional (meth)acrylic monomer, a multifunctional (meth)acrylic monomer, a photopolymerization initiator, and a thermoplastic resin with a block or graft structure. The thermoplastic resin has a viscosity range of 0.001 Pa·s to 500 Pa·s at 25°C, and is derived from styrene, providing enhanced creep resistance and adhesion.
The composition achieves excellent adhesion and creep resistance, with a gel fraction of the cured product ranging from 25% to 60% by mass, and a glass transition temperature suitable for various substrates, thereby addressing the limitations of previous adhesive compositions.
Smart Images

Figure 2025065196000001 
Figure 2025065196000002 
Figure 2025065196000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a photocurable resin composition. The present invention also relates to a pressure-sensitive adhesive sheet using the photocurable resin composition, and a method for producing a laminate using the photocurable resin composition. [Background technology]
[0002] Adhesives are used to bond electronic components inside electronic devices such as smartphones and PCs. In a typical method of bonding using adhesives, first, an adhesive sheet is prepared with separators arranged on both sides of the adhesive, and then the adhesive sheet is cut into a desired shape. Then, one separator is peeled off from the cut adhesive sheet, and one side of the exposed adhesive is bonded to a first adherend, and then the other separator is peeled off, and the other side of the exposed adhesive is bonded to a second adherend. In this method, a part of the adhesive sheet is discarded after cutting, resulting in waste.
[0003] In response to this, a method has been considered in which a pressure-sensitive adhesive composition is printed in a desired shape and then attached to an adherend, which can reduce the generation of waste. As an invention relating to an adhesive composition that can be used in such a method, for example, Patent Document 1 discloses an invention for providing a radiation-curable adhesive composition that allows fine patterning and exhibits high adhesion to various adherends such as metals and plastics. Patent Document 1 describes a radiation-curable adhesive composition that contains 10 to 70% by weight of an aromatic ring-free ethylenically unsaturated monomer, 1 to 10% by weight of a photopolymerization initiator, and 10 to 55% by weight of a crosslinking agent. Patent Document 2 discloses an invention for providing a photocurable adhesive composition that, even when irradiated with light in the presence of oxygen, gives a laminate having adhesive strength equivalent to that in the absence of oxygen. Patent Document 2 describes a photocurable adhesive composition that contains (A) a (meth)acrylate oligomer, (B) a monofunctional (meth)acrylic monomer, (C) a difunctional to tetrafunctional (meth)acrylic monomer, (D) a photoinitiator, (E) a tackifier having a softening point of 70 to 150°C, and (F) a liquid plasticizer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-216742 A [Patent Document 2] International Publication No. 2016 / 163152 Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, the method of printing the adhesive composition into a desired shape and then laminating it to an adherend can suppress the generation of waste. On the other hand, as a method of curing the adhesive composition, a method of light irradiation is desirable to avoid heating the adherend, but if the adhesive composition is not covered with a separator and exposed to oxygen during curing, the outermost surface does not cure and sufficient adhesion may not be obtained. Therefore, in order to prevent oxygen inhibition, it was necessary to seal the adhesive composition with a separator and irradiate light under an inert gas atmosphere to cause the reaction to proceed. In addition, even if the adhesiveness is improved by using a material that is not easily inhibited by oxygen, the creep retention may be low, and a photocurable resin composition that is excellent in both adhesion and creep resistance was required.
[0006] The present invention aims to provide a photocurable resin composition having excellent adhesion and creep resistance. It is also an object of the present invention to provide a pressure-sensitive adhesive sheet using the photocurable resin composition, and a method for producing a laminate using the photocurable resin composition. [Means for solving the problem]
[0007] The present disclosure 1 relates to a photocurable resin composition comprising a monofunctional (meth)acrylic monomer, a polyfunctional (meth)acrylic monomer, a photopolymerization initiator, and a thermoplastic resin, the thermoplastic resin having a block structure or a graft structure and having a viscosity at 25°C of 0.001 Pa s or more and 500 Pa s or less. Disclosure 2 is the photocurable resin composition of Disclosure 1, wherein the thermoplastic resin contains a thermoplastic resin having a structure derived from styrene. Disclosure 3 relates to the photocurable resin composition of Disclosure 2, in which the thermoplastic resin having a structure derived from styrene is a (meth)acrylic / styrene copolymer. The present disclosure 4 is the photocurable resin composition of the present disclosure 2 or 3, in which the content of the structure derived from styrene in the thermoplastic resin having the structure derived from styrene is 3 mass % or more. The present disclosure 5 is the photocurable resin composition according to the present disclosure 1, 2, 3 or 4, wherein the thermoplastic resin contains a triblock copolymer, and the content of the triblock copolymer in the thermoplastic resin is 50 mass % or more. The present disclosure 6 is the photocurable resin composition of the present disclosure 1, 2, 3, 4, or 5, wherein the thermoplastic resin has a weight average molecular weight of 100,000 or more and 500,000 or less. The present disclosure 7 is the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, or 6, in which the content of the thermoplastic resin in the photocurable resin composition is 1% by mass or more and 60% by mass or less. The present disclosure 8 is the photocurable resin composition of the present disclosure 7, in which the content of the thermoplastic resin in the photocurable resin composition is 10% by mass or more and 40% by mass or less. Disclosure 9 is the photocurable resin composition of Disclosure 1, 2, 3, 4, 5, 6, 7, or 8, wherein the content of the polyfunctional (meth)acrylic monomer in the photocurable resin composition is 0.3% by mass or more and 40% by mass or less. The present disclosure 10 relates to a method for producing the above-mentioned photocurable resin composition using a light source having a wavelength of 395 nm and an illuminance of 500 mW / cm 2 The UV irradiation dose is 3000mJ / cm 2 The photocurable resin composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, or 9, wherein the gel fraction of the cured product obtained by irradiating the photocurable resin composition so as to satisfy the above condition is 25% by mass or more and 60% by mass or less. The present disclosure 11 is a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer including a cured product of the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. The present disclosure 12 is a pressure-sensitive adhesive sheet according to the present disclosure 11, comprising a substrate and a pressure-sensitive adhesive layer comprising a cured product of the photocurable resin composition on at least one surface of the substrate. The present disclosure 13 is a method for producing a laminate, comprising the steps of printing the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, and attaching an adherend using the printed photocurable resin composition. The present disclosure 14 is the method for producing a laminate according to the present disclosure 13, wherein the method for printing the photocurable resin composition is screen printing, inkjet printing, or flexographic printing. The present invention will be described in detail below.
[0008] The present inventors have investigated the possibility of forming a photocurable resin composition containing a monofunctional (meth)acrylic monomer, a polyfunctional (meth)acrylic monomer, a photopolymerization initiator, and a thermoplastic resin having a block structure or a graft structure, while adjusting the viscosity to a specific range from the viewpoint of printability, etc. As a result, they have found that a photocurable resin composition having excellent adhesiveness and creep resistance can be obtained, and have completed the present invention.
[0009] The photocurable resin composition of the present invention contains a monofunctional (meth)acrylic monomer. The monofunctional (meth)acrylic monomer is a polymerizable monomer that is polymerized by a reaction with a photopolymerization initiator described later. By containing the monofunctional (meth)acrylic monomer, the photocurable resin composition of the present invention has excellent adhesion to various substrates. In this specification, the term "(meth)acrylic" means acrylic or methacrylic, the term "(meth)acrylic monomer" means a monomer having a (meth)acryloyl group, and the term "(meth)acryloyl" means acryloyl or methacryloyl. In addition, in this specification, the term "monofunctional (meth)acrylic monomer" means a monomer having one (meth)acryloyl group in one molecule.
[0010] Examples of the monofunctional (meth)acrylic monomer include a monofunctional (meth)acrylic acid ester compound, a monofunctional (meth)acrylamide compound, and a monofunctional (meth)acrylimide compound.
[0011] Examples of the monofunctional (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. , cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrahydrofurfuryl alcohol acrylic acid polymer ester, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-Octafluoropentyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(((butylamino)carbonyl)oxy)ethyl (meth)acrylate, (3-propyloxetan-3-yl)methyl (meth)acrylate, (3-butyloxetan-3-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)ethyl (meth)acrylate, (3-ethyl oxetan-3-yl)propyl (meth)acrylate, (3-ethyloxetan-3-yl)butyl (meth)acrylate, (3-ethyloxetan-3-yl)pentyl (meth)acrylate, (3-ethyloxetan-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-isobutyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-cyclohexyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, cyclic trimethylolpropane formal acrylate, etc., In this specification, the term "(meth)acrylate" means acrylate or methacrylate.
[0012] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide.
[0013] Examples of the monofunctional (meth)acrylimide compound include N-(meth)acryloyloxyethylhexahydrophthalimide.
[0014] The preferred lower limit of the content of the monofunctional (meth)acrylic monomer in the photocurable resin composition of the present invention is 20% by mass, and the preferred upper limit is 90% by mass. By having the content of the monofunctional (meth)acrylic monomer in this range, the resulting photocurable resin composition has better adhesion to various substrates. The more preferred lower limit of the content of the monofunctional (meth)acrylic monomer is 30% by mass, and the more preferred upper limit is 85% by mass.
[0015] The photocurable resin composition of the present invention contains a polyfunctional (meth)acrylic monomer. The polyfunctional (meth)acrylic monomer is a polymerizable monomer that is polymerized by the reaction of a photopolymerization initiator described below, and the polyfunctional (meth)acrylic monomer serves as a crosslinking component. In this specification, the above-mentioned "polyfunctional (meth)acrylic monomer" means a monomer having two or more (meth)acryloyl groups in one molecule.
[0016] Examples of the polyfunctional (meth)acrylic monomer include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylic acid ester compounds, and polyfunctional epoxy (meth)acrylates. In this specification, the above-mentioned "epoxy (meth)acrylate" refers to a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.
[0017] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting an isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.
[0018] Examples of the isocyanate compound that is a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.
[0019] As the isocyanate compound serving as a raw material for the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by reacting a polyol with an excess of an isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0020] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, and mono(meth)acrylates or di(meth)acrylates of trihydric alcohols. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin.
[0021] Examples of the polyfunctional (meth)acrylic acid ester compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-Propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadiene Di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl(meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylol dimethacrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate , pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0022] Examples of the polyfunctional epoxy(meth)acrylate include bisphenol A type epoxy(meth)acrylate, bisphenol F type epoxy(meth)acrylate, bisphenol E type epoxy(meth)acrylate, and caprolactone modified versions of these.
[0023] The content of the polyfunctional (meth)acrylic monomer in the photocurable resin composition of the present invention is preferably 0.3% by mass at the lower limit and 40% by mass at the upper limit. By setting the content of the polyfunctional (meth)acrylic monomer in this range, the resulting photocurable resin composition has better adhesion to various substrates and creep resistance. The content of the polyfunctional (meth)acrylic monomer is more preferably 0.5% by mass at the lower limit and 30% by mass at the upper limit.
[0024] The photocurable resin composition of the present invention preferably contains a compound having a cyclic structure containing a nitrogen atom (hereinafter also referred to as "nitrogen-containing ring compound") as a polymerizable monomer. By containing the nitrogen-containing ring compound, the photocurable resin composition obtained has better photocurability in the presence of oxygen. The nitrogen-containing ring compound may be one contained in the monofunctional (meth)acrylic monomer or the polyfunctional (meth)acrylic monomer, or may not be one contained in the monofunctional (meth)acrylic monomer or the polyfunctional (meth)acrylic monomer.
[0025] The nitrogen-containing cyclic compound preferably contains at least one selected from the group consisting of monofunctional radically polymerizable monomers having a lactam structure and maleimide derivatives, and more preferably contains a maleimide derivative. The reaction system of the monofunctional radical polymerizable monomer having the lactam structure and the maleimide derivative basically proceeds by a hydrogen abstraction (Type II) reaction. Photoradical polymerization by hydrogen abstraction reaction is not easily inhibited by oxygen, and can increase the surface curability. In addition, photoradical polymerization by hydrogen abstraction reaction does not give a linear polymer as in cleavage (Type I) reaction, but gives a branched polymer, and the cohesive strength is also high. Therefore, by containing the monofunctional radical polymerizable monomer having the lactam structure and the maleimide derivative, the photocurable resin composition obtained can give a cured product that is less likely to cause bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength.
[0026] Among the above maleimide derivatives, examples of the monofunctional maleimide include N-cyclohexylmaleimide, N-laurylmaleimide, 4-hydroxyphenylmaleimide, N-(4-carboxycyclohexylmethyl)maleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-methylmaleimide, and N-ethylmaleimide. Examples of such maleimide include N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-(2,4,6-tribromophenyl)maleimide, N-(3-(triethoxysilyl)propyl)maleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, N-(2-methoxyphenyl)maleimide, N-(2,4,6-trichlorophenyl)maleimide, and N-(1-hydroxyphenyl)maleimide. Among these, it is desirable to select a maleimide derivative that does not have a structure in which hydrogen is bonded to a heteroatom from the viewpoint of increasing the reaction rate. Also, from the viewpoint of improving adhesive strength, a maleimide derivative that has a structure in which hydrogen is bonded to a heteroatom may be used. Specifically, the monofunctional maleimide is preferably at least one selected from the group consisting of N-cyclohexylmaleimide, 4-hydroxyphenylmaleimide, and N-(4-carboxycyclohexylmethyl)maleimide, and more preferably N-cyclohexylmaleimide. Among the maleimide derivatives, examples of polyfunctional maleimides include N,N'-methylene bismaleimide, N,N'-trimethylene bismaleimide, N,N'-dodecamethylene bismaleimide, N,N'-(4,4'-diphenylmethane) bismaleimide, 1,4-dimaleimidecyclohexane, isophorone bisurethane bis(N-ethylmaleimide), N,N'-p-phenylene bismaleimide, N,N'-m-phenylene bismaleimide, N,N'-m-toluylene bismaleimide, and N,N'-4,4'-biphenyl Examples of the maleimide derivatives include N,N'-4,4'-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4'-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4'-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4'-diphenylpropane bismaleimide, N,N'-4,4'-diphenylether bismaleimide, N,N'-3,3'-diphenylsulfone bismaleimide, and N,N'-4,4'-diphenylsulfone bismaleimide. From the viewpoint of increasing the reaction rate, the above monofunctional maleimide may be used in combination with these polyfunctional maleimides as the maleimide derivatives, but it is not preferable to use a large amount of polyfunctional maleimide in combination because the gel fraction increases.
[0027] The monofunctional radically polymerizable monomer having a lactam structure is preferably a compound represented by the following formula (1).
[0028] [ka]
[0029] In the formula (1), n represents an integer of 2 to 6.
[0030] Examples of the compound represented by the above formula (1) include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, etc. Among these, N-vinyl-ε-caprolactam is preferred.
[0031] The content ratio of the nitrogen-containing ring compound in the photocurable resin composition of the present invention is preferably 0.1% by mass at the lower limit, and 30% by mass at the upper limit. By making the content ratio of the nitrogen-containing ring compound within this range, the obtained pressure-sensitive adhesive sheet has better surface curing properties and adhesion to various substrates. The content ratio of the nitrogen-containing ring compound is more preferably 0.5% by mass at the lower limit, and 25% by mass at the upper limit.
[0032] The photocurable resin composition of the present invention contains a photopolymerization initiator. The photopolymerization initiator preferably contains at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators. By using at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators as the photopolymerization initiator, the obtained cured product is less likely to suffer from bleeding due to a decrease in surface curability, or cohesive failure due to a decrease in surface curability and cohesive force. The photopolymerization initiator more preferably contains a polymer type photopolymerization initiator.
[0033] Examples of the polymer type photopolymerization initiator include a polymer of ethyl (2,4,6-trimethylbenzoyl)-phenyl phosphonate, polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butanoylphenyl)piperazine)propionate, and bis(benzophenone-2-carboxylic acid) polyethylene glycol ester.
[0034] Among the above polymer type photopolymerization initiators, commercially available ones include, for example, Omnipol TP, Omnipol 910, Omnipol 2702 (all manufactured by IGM Resins), and the like.
[0035] The hydrogen abstraction type photopolymerization initiator is preferably a benzophenone-based photopolymerization initiator.The benzophenone-based photopolymerization initiator can be exemplified by benzophenone, 4-chlorobenzophenone, 4,4'-dimethylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, o-benzoyl methyl benzoate, 3,3'-dimethyl-4-methoxybenzophenone, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 4-morpholinobenzophenone, 4,4'-diphenoxybenzophenone, 4-hydroxybenzophenone, 2-carboxybenzophenone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methyl-propionyl)-benzyl)-phenyl)-2-methyl-propan-1-one, 1-(4-(4-benzoylphenylthio)phenyl)-2-tosyl-2-methyl-1-propanone, 3-ketocoumarin, etc.
[0036] As the photopolymerization initiator, a cleavage type photopolymerization initiator can also be used. Examples of the cleavage type photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0037] The content of the photopolymerization initiator in the photocurable resin composition of the present invention is preferably 1% by mass at the lower limit and 15% by mass at the upper limit. By having the content of the photopolymerization initiator in this range, the resulting photocurable resin composition has better storage stability and curability, and the resulting pressure-sensitive adhesive sheet has better adhesion to various substrates. The more preferred lower limit of the content of the photopolymerization initiator is 3% by mass, and the more preferred upper limit is 8% by mass.
[0038] The photocurable resin composition of the present invention contains a thermoplastic resin. The thermoplastic resin has a block structure or a graft structure. By containing the thermoplastic resin having the block structure or the graft structure, the photocurable resin composition of the present invention has excellent creep resistance. In particular, the thermoplastic resin preferably has a block structure. The block structure or the graft structure may be present in any part of the molecule of the thermoplastic resin, and a random structure may be present in the other part. Even if the thermoplastic resin is a polymer of two or more monomers having a common structure, if the two or more monomers are different compounds and have a block structure or a graft structure, it is treated as a thermoplastic resin having a block structure or a graft structure. An example of such a polymer is an acrylic triblock copolymer derived from three types of acrylic monomers.
[0039] The thermoplastic resin preferably contains a thermoplastic resin having a structure derived from styrene or a thermoplastic resin having a structure derived from a (meth)acrylic compound. By containing the thermoplastic resin having a structure derived from styrene or a thermoplastic resin having a structure derived from a (meth)acrylic compound, the resulting photocurable resin composition has better creep resistance. In particular, the thermoplastic resin more preferably contains a thermoplastic resin having a structure derived from styrene.
[0040] Examples of the thermoplastic resin having a structure derived from styrene include (meth)acrylic / styrene copolymer, butadiene / styrene, isoprene / styrene, ethylenebutylene / styrene, ethylenepropylene / styrene, etc. Among them, from the viewpoints of compatibility with monofunctional (meth)acrylic monomers and polyfunctional (meth)acrylic monomers and improvement of creep resistance, (meth)acrylic / styrene copolymer is preferred.
[0041] The preferred lower limit of the content of the styrene-derived structure in the thermoplastic resin having the styrene-derived structure is 3% by mass. When the content of the styrene-derived structure is 3% by mass or more, the resulting photocurable resin composition has better creep resistance. The more preferred lower limit of the content of the styrene-derived structure is 4% by mass. In addition, from the viewpoints of compatibility with monofunctional (meth)acrylic monomers and polyfunctional (meth)acrylic monomers and adhesion to an adherend, the upper limit of the content of the styrene-derived structure in the thermoplastic resin having a styrene-derived structure is preferably 40 mass%, and more preferably 30 mass%.
[0042] Examples of the thermoplastic resin having a structure derived from the above-mentioned (meth)acrylic compound include poly(meth)acrylate, acrylonitrile / styrene / (meth)acrylic copolymer, (meth)acrylic / styrene copolymer, ethylene / (meth)acrylic copolymer / acrylic / methacrylic copolymer, etc. Among them, from the viewpoint of compatibility with monofunctional (meth)acrylic monomers and polyfunctional (meth)acrylic monomers and improvement of creep resistance, (meth)acrylic / styrene copolymer is preferred.
[0043] The thermoplastic resin preferably contains a triblock copolymer. By containing the thermoplastic resin which is a triblock copolymer, the resulting photocurable resin composition has better creep resistance. Among them, it is more preferable that the thermoplastic resin contains a (meth)acrylic / styrene-based triblock copolymer as the ABA type triblock copolymer.
[0044] The lower limit of the content of the triblock copolymer in the thermoplastic resin is preferably 50% by mass. When the content of the triblock copolymer is 50% by mass or more, the resulting photocurable resin composition has better creep resistance. The lower limit of the content of the triblock copolymer is more preferably 70% by mass. The content of the triblock copolymer may be 100% by mass, that is, the thermoplastic resin may contain only the triblock copolymer.
[0045] The thermoplastic resin has a weight average molecular weight of preferably 100,000 at the lower limit and 500,000 at the upper limit. When the weight average molecular weight of the thermoplastic resin is within this range, the resulting photocurable resin composition has better creep resistance. The weight average molecular weight of the thermoplastic resin is more preferably 150,000 at the lower limit and 400,000 at the upper limit. The weight average molecular weight can be determined by, for example, measuring the molecular weight distribution in terms of polystyrene using gel permeation chromatography (GPC). Specifically, for example, it can be determined by measuring under the following conditions using gel permeation chromatography (Waters Corporation, "2690 Separations Module" or the like). Solvent: Tetrahydrofuran Sample flow rate: 1mL / min Detector: Differential refractive index RI Column: GPC KF-806L (Showa Denko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL
[0046] The preferred lower limit of the content of the thermoplastic resin in the photocurable resin composition of the present invention is 1% by mass, and the preferred upper limit is 60% by mass. By having the content of the thermoplastic resin in this range, the resulting photocurable resin composition has better creep resistance. The more preferred lower limit of the content of the thermoplastic resin is 10% by mass, and the more preferred upper limit is 40% by mass.
[0047] The photocurable resin composition of the present invention preferably further contains a tackifier. Examples of the tackifier include rosin-based resins and terpene-based resins.
[0048] The rosin-based resin may, for example, be rosin diol. The rosin diol is not particularly limited as long as it is a rosin-modified diol having two rosin skeletons and two hydroxyl groups in the molecule. Diols having a rosin component in the molecule are called rosin polyols, and these include polyether types such as polypropylene glycol (PPG) in which the skeleton excluding the rosin component is polyether, and polyester types such as condensation polyester polyols, lactone polyester polyols, and polycarbonate diols. Examples of the rosin diol include rosin ester obtained by reacting rosin with a polyhydric alcohol, epoxy-modified rosin ester obtained by reacting rosin with an epoxy compound, and modified rosin having a hydroxyl group, such as polyether having a rosin skeleton, etc. These can be produced by conventionally known methods.
[0049] Examples of the rosin component include abietic acid, abietic acid derivatives such as dehydroabietic acid, dihydroabietic acid, tetrahydroabietic acid, diabietic acid, and neoabietic acid, pimaric acid type resin acids such as levopimaric acid, hydrogenated rosins obtained by hydrogenating these, and disproportionated rosins obtained by disproportionating these.
[0050] Among the above rosin-based resins, commercially available ones include, for example, Pine Crystal D-6011, Pine Crystal KE-615-3, Pine Crystal KR-614, Pine Crystal KE-100, Pine Crystal KE-311, Pine Crystal KE-359, Pine Crystal KE-604, Pine Crystal D-6250 (all manufactured by Arakawa Chemical Industries Co., Ltd.), and the like.
[0051] Examples of the terpene resin include terpene phenol resins. The terpene phenol resin is a copolymer of phenol and a terpene resin, which is an essential oil component obtained from natural products such as rosin and orange peel, and also includes partially hydrogenated terpene phenol resins in which at least a portion of the copolymer is hydrogenated, or fully hydrogenated terpene phenol resins in which the copolymer is completely hydrogenated. Here, the fully hydrogenated terpene phenolic resin is a terpene resin obtained by substantially completely hydrogenating a terpene phenolic resin, and the partially hydrogenated terpene phenolic resin is a terpene resin obtained by partially hydrogenating a terpene phenolic resin. The terpene phenolic resin has a double bond derived from a terpene and an aromatic ring double bond derived from a phenol. Therefore, the fully hydrogenated terpene phenolic resin means a resin in which both the terpene portion and the phenol portion are completely or almost hydrogenated, and the partially hydrogenated terpene phenolic resin means a resin in which the degree of hydrogenation of these portions is not complete but partial. The hydrogenation method and reaction form are not particularly limited. Among the above terpene phenol-based resins, examples of commercially available ones include YS Polystar NH (fully hydrogenated terpene phenol-based resin) manufactured by Yasuhara Chemical Co., Ltd.
[0052] The preferred lower limit of the content of the tackifier in the photocurable resin composition of the present invention is 5% by mass, and the preferred upper limit is 50% by mass. By having the content of the tackifier in this range, the resulting photocurable resin composition has better adhesion to various substrates. The more preferred lower limit of the content of the tackifier is 10% by mass, and the more preferred upper limit is 40% by mass.
[0053] The photocurable resin composition of the present invention may contain a filler from the viewpoint of improving printability by adjusting the viscosity. As the filler, an inorganic filler or an organic filler can be used. Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate. Examples of the organic filler include polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, and (meth)acrylic polymer fine particles. Of these, silica is preferred, and fumed silica is more preferred.
[0054] The preferred lower limit of the filler content in the photocurable resin composition of the present invention is 0.3% by mass, and the preferred upper limit is 15% by mass. By having the filler content within this range, the obtained photocurable resin composition can easily adjust the viscosity while maintaining excellent adhesiveness. The more preferred lower limit of the filler content is 0.5% by mass, and the more preferred upper limit is 10% by mass.
[0055] The photocurable resin composition of the present invention may contain an antifoaming agent from the viewpoint of improving printability, etc. Examples of the defoaming agent include silicone-based defoaming agents, acrylic polymer-based defoaming agents, vinyl ether polymer-based defoaming agents, and olefin polymer-based defoaming agents.
[0056] The content of the defoaming agent in the photocurable resin composition of the present invention is preferably 0.3% by mass at the lower limit and 5% by mass at the upper limit. By setting the content of the defoaming agent in this range, the photocurable resin composition obtained has better printability. The content of the defoaming agent is more preferably 0.5% by mass at the lower limit and 3% by mass at the upper limit.
[0057] The photocurable resin composition of the present invention may further contain various known additives such as a plasticizer, a silane coupling agent, a sensitizer, a heat curing agent, a curing retarder, an antioxidant, a storage stabilizer, and a dispersant, as long as the object of the present invention is not impaired. Moreover, from the viewpoint of preventing a decrease in photoreactivity, it is preferable that the photocurable resin composition of the present invention is substantially free of organic solvents. Specifically, it is preferable that the content of organic solvents in the photocurable resin composition is 1.5 mass% or less.
[0058] The photocurable resin composition of the present invention can be prepared, for example, by using a mixer to mix the monofunctional (meth)acrylic monomer, the polyfunctional (meth)acrylic monomer, the photopolymerization initiator, the thermoplastic resin, and additives added as necessary. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.
[0059] The photocurable resin composition of the present invention is suitable for printing. If a pressure-sensitive adhesive layer is formed by applying a desired pattern on an adherend (substrate) by printing, there is an advantage that the cutting process can be omitted compared to the case where a sheet-shaped pressure-sensitive adhesive is cut just before lamination to obtain a pressure-sensitive adhesive of a desired shape. As a result, it is possible to suppress the generation of waste and reduce the environmental load.
[0060] The lower limit of the viscosity of the photocurable resin composition of the present invention at 25°C is 0.001 Pa·s and the upper limit is 500 Pa·s. When the viscosity is within this range, the photocurable resin composition of the present invention is suitable for printing. The lower limit of the viscosity is preferably 0.01 Pa·s and the upper limit is preferably 300 Pa·s, more preferably 0.1 Pa·s and the upper limit is more preferably 100 Pa·s. The viscosity can be measured, for example, by using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer and selecting an appropriate rotation speed of 1 to 100 rpm from the optimum torque number in each viscosity range with a cone plate of CP1.
[0061] The photocurable resin composition of the present invention is exposed to a wavelength of 395 nm and an illuminance of 500 mW / cm 2 The UV irradiation dose is 3000mJ / cm 2 The preferred lower limit of the gel fraction of the cured product obtained by irradiating the resin so as to satisfy the above condition is 25% by mass, and the preferred upper limit is 60% by mass. When the gel fraction of the cured product is within this range, the resulting photocurable resin composition has better adhesion and creep resistance after curing. The lower limit of the gel fraction of the cured product is more preferably 30% by mass, and the upper limit is more preferably 50% by mass. The gel fraction of the cured product can be measured by the following method. That is, first, the photocurable resin composition was exposed to a 395 nm wavelength and 500 mW / cm illuminance. 2 The UV irradiation dose is 3000mJ / cm 2 A cured product is obtained by irradiating the cured product so that the cured product is 0.15 g. After weighing 0.15 g of the cured product obtained, the product is immersed in 30 g of tetrahydrofuran and immersed in the product while shaking at 23°C for 24 hours. The cured product is then removed through a 200 mesh filter and dried by heating at 110°C for 1 hour. The mass of the cured product is then measured, and the gel fraction can be calculated using the following formula. Gel fraction (mass%) = (W2 / W1) x 100 W1: Mass of the cured product before immersion in tetrahydrofuran at 23°C W2: Mass of the cured product after immersion in tetrahydrofuran at 23°C, removal, and drying
[0062] The photocurable resin composition of the present invention is prepared by coating the photocurable resin composition on a substrate and applying the composition at a wavelength of 395 nm and an illuminance of 500 mW / cm 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2The glass transition temperature of the cured product obtained by irradiating the photosensitive resin composition so as to satisfy the above condition is preferably −10° C. at the lower limit and 25° C. at the upper limit. When the glass transition temperature of the cured product is within this range, the photocurable resin composition obtained has better adhesion to various substrates. The glass transition temperature of the cured product is more preferably −5° C. at the lower limit and 15° C. at the upper limit. The glass transition temperature of the cured product can be measured by the following method. That is, first, the photocurable resin composition is applied onto a release PET film as a substrate, and then, using an ultraviolet ray irradiation device, the composition is irradiated with ultraviolet light having a wavelength of 395 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the photocurable resin composition so as to obtain a cured product, the photocurable resin composition is cured. The glass transition temperature of the resulting cured product can be determined as the tan δ peak temperature when dynamic viscoelasticity measurement is performed under the following conditions using a dynamic viscoelasticity measuring device. As the dynamic viscoelasticity measuring device, for example, DVA-200 (manufactured by IT Measurement & Control Co., Ltd.) can be used. <Condition> Shear Method Measurement temperature: -70℃~200℃ Heating rate: 1℃ / min Distortion: 0.1% Frequency: 1Hz
[0063] The photocurable resin composition of the present invention can form an adhesive layer by curing it by irradiation with ultraviolet light, and the method of use may be to form an adhesive layer on a substrate (separator) to prepare an adhesive sheet that can be transferred to an adherend, or to form an adhesive layer directly on an adherend. In the method of forming an adhesive layer directly on an adherend, the number of times of lamination can be minimized and air bubbles can be prevented from entering the interface during lamination. On the other hand, in the method of forming an adhesive layer on a substrate (separator), the adhesive layer is placed on the adherend by transfer, so there is an advantage that there are few restrictions on construction.
[0064] The present invention also includes a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing a cured product of the photocurable resin composition of the present invention. The pressure-sensitive adhesive sheet of the present invention may be a non-support type pressure-sensitive adhesive sheet that does not have a substrate, or it may be a supported type pressure-sensitive adhesive sheet, i.e., a pressure-sensitive adhesive sheet having a substrate and a pressure-sensitive adhesive layer containing a cured product of the photocurable resin composition of the present invention on at least one surface of the substrate.
[0065] When the pressure-sensitive adhesive sheet of the present invention has a substrate, it may be a single-sided pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer on one side of a substrate, or a double-sided pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layers on both sides.
[0066] Examples of the substrate include sheets made of resins such as acrylic, olefin, polycarbonate, vinyl chloride, ABS, polyethylene terephthalate (PET), nylon, urethane, and polyimide, sheets having a mesh structure, and sheets with holes.
[0067] The present invention also includes a method for producing a laminate, which comprises the steps of printing the photocurable resin composition of the present invention and attaching an adherend using the printed photocurable resin composition.
[0068] In the method for producing the laminate of the present invention, examples of the method for printing the photocurable resin composition of the present invention include screen printing, inkjet printing, flexographic printing, gravure printing, slot die coating, knife coating, spray coating, spin coating, stencil printing, dispensing, jet dispensing, reverse offset printing, etc. Among these, screen printing, inkjet printing, or flexographic printing is preferred, and screen printing is more preferred.
[0069] Examples of the material of the adherend include metals such as stainless steel and aluminum, and resins. Effect of the Invention
[0070] According to the present invention, it is possible to provide a photocurable resin composition having excellent adhesion and creep resistance. Also, according to the present invention, it is possible to provide a pressure-sensitive adhesive sheet using the photocurable resin composition, and a method for producing a laminate using the photocurable resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0072] (Examples 1 to 13, Comparative Examples 1 to 5) According to the compounding ratios shown in Tables 1 and 2, each material was mixed with a planetary mixer (Thinky Corporation, "Awatori Rentaro") to obtain each photocurable resin composition of the examples and comparative examples. Details of the materials indicated by abbreviations in the table are as follows. (Monofunctional (meth)acrylic monomer) CBA: Ethyl carbitol acrylate (Osaka Organic Chemical Industry Co., Ltd., "Viscoat #190") MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) M-140: N-Acryloyloxyethylhexahydrophthalimide (Toagosei Co., Ltd., nitrogen-containing ring compound) (Polyfunctional (meth)acrylic monomer) · UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) (Nitrogen-containing ring compound) CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai Co., Ltd.) (Photopolymerization initiator) Omnipol TP: Ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate polymer (IGM Resins, polymeric photoinitiator) Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butanoylphenyl)piperazine)propionate (IGM Resins, polymeric photoinitiator) (thermoplastic resin) Acrylic polymer A: Acrylic random copolymer (manufactured by Saiden Chemical Industry Co., Ltd., weight average molecular weight 460,000, monomer composition (butyl acrylate and 2-ethylhexyl acrylate)) ·LA2330: Acrylic triblock copolymer (Kuraray, weight average molecular weight 120,000) Acrylic / styrene polymer A: styrene / butyl acrylate / styrene triblock copolymer (styrene-derived structure content: 20% by mass, weight average molecular weight: 300,000, triblock ratio: 90%) Acrylic / styrene polymer B: Styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structure: 2.8% by mass, weight average molecular weight: 300,000, triblock ratio: 90%) Acrylic / styrene polymer C: Styrene / butyl acrylate / styrene triblock copolymer (styrene-derived structure content: 20% by mass, weight average molecular weight: 300,000, triblock ratio: 50%) Acrylic / styrene polymer D: styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structure: 20% by mass, weight average molecular weight: 300,000, triblock ratio: 40%) Acrylic graft polymer A: The polymer (weight average molecular weight 480,000) obtained in the step "Synthesis of acrylic graft polymer A" described below, which corresponds to poly(meth)acrylate. (tackifier) KE-359: Rosin ester (Arakawa Chemical Industries, Ltd.) D-6011: Rosindiol (Arakawa Chemical Industries, Ltd.) (Filler) R805: Fumed silica (manufactured by Nippon Aerosil Co., Ltd.) (Antifoaming agent) ·KS-66: Silicone-based defoamer (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0073] (Synthesis of Acrylic Graft Polymer A) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared. After adding 73.8 parts by mass of butyl acrylate, 0.2 parts by mass of acrylic acid, 20 parts by mass of ethylene-butylene macromonomer, 0.014 parts by mass of lauryl mercaptan, and 80 parts by mass of ethyl acetate to the reactor, the reactor was heated to start reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to the reactor, and polymerization was started under reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added one hour and two hours after the start of polymerization, and further 0.05 parts by mass of t-hexylperoxypivalate was added four hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution of acrylic graft polymer A having a solid content of 60 mass % and a weight average molecular weight of 480,000 was obtained. The weight average molecular weight of the obtained acrylic graft polymer A was measured using gel permeation chromatography (Waters Corporation, "2690 Separations Module" or the like) under the following conditions. <Condition> Solvent: Tetrahydrofuran Sample flow rate: 1mL / min Detector: Differential refractive index RI Column: GPC KF-806L (Showa Denko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL
[0074] (viscosity) 0.4 mL of each of the obtained photocurable resin compositions was taken, and the viscosity was measured using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer with a CP1 cone plate at 25° C. and 10 rpm. The results are shown in Tables 1 and 2.
[0075] (Gel fraction of cured product) Each of the obtained photocurable resin compositions was applied onto a release PET film (manufactured by Nippa Corporation, "1-E", thickness 50 μm) using an applicator. Then, using a batch-type UV LED curing device (manufactured by CSS, "UV-LED PROCESSOR LSS-61"), the composition was cured with a wavelength of 395 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product having a thickness of 50 μm was obtained by irradiating the film so as to obtain a thickness of 50 μm. Thereafter, the surface facing the atmosphere was sealed with a release PET film (manufactured by Nippa Corporation, "1-C", thickness 38 μm) to obtain a laminate. Both release films were peeled off from the obtained laminate, and 0.15 g of the cured product of the photocurable resin composition was weighed into a glass bottle, which was then immersed in 30 g of tetrahydrofuran and immersed with shaking at 23°C for 24 hours. The cured product was then removed through a 200 mesh filter and heated and dried at 110°C for 1 hour. The mass of the cured product was then measured, and the gel fraction was calculated using the following formula. The results are shown in Tables 1 and 2. Gel fraction (mass%) = (W2 / W1) x 100 W1: Mass of the cured product before immersion in tetrahydrofuran at 23°C W2: Mass of the cured product after immersion in tetrahydrofuran at 23°C, removal, and drying
[0076] (Glass transition temperature of the cured product) Both release films were peeled off from the laminate obtained in the same manner as in "(Gel fraction of cured product)" above, and the cured product of the photocurable resin composition was laminated to a thickness of 1 mm, which was then attached to a jig and subjected to dynamic viscoelasticity measurement under the following conditions using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") to obtain a viscoelasticity chart. The tan δ peak temperature in the obtained viscoelasticity chart was determined as the glass transition temperature. The results are shown in Tables 1 and 2. <Condition> Shear Method Measurement temperature: -70~200℃ Heating rate: 1℃ / min Distortion: 0.1% Frequency: 1Hz
[0077] <Evaluation> The photocurable resin compositions obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 and 2.
[0078] (180° peel adhesive strength) Each of the obtained photocurable resin compositions was applied to the inner treated surface of an easily adhesive polyester film ("Cosmoshine A4100" manufactured by Toyobo Co., Ltd.) with an applicator. After that, without sealing the coated surface, the coated surface was cured in an atmospheric environment with a batch-type UV LED curing device ("UV-LED PROCESSOR LSS-61" manufactured by CSS Co., Ltd.) at a wavelength of 395 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product with a thickness of 50 μm was obtained by irradiating the film so that the thickness of the film was 50 μm. The illuminance and the accumulated light quantity were measured using an ultraviolet irradiation meter UVR-T2 and a light receiving unit UD-T36T2 (manufactured by TOPCON). Next, the air surface was sealed with a release PET film (manufactured by Nippa, "1-C", thickness 38 μm) and cut to a width of 25 mm and a length of 200 mm (adhering surface 25 mm x 125 mm) to prepare a laminated film. After that, the release PET film was peeled off from the laminated film, and the exposed surface was attached to a SUS substrate and pressed by moving a 2 kg roller back and forth once to obtain a test specimen. The obtained test specimen was stored in an environment of 25 ° C for 24 hours, and the 180 ° peel adhesive strength was measured by performing a 180 ° peel at a speed of 300 mm / min using a universal testing machine (manufactured by A & D, "Tensilon RTI-1310").
[0079] (Creep resistance) The laminate obtained in the same manner as in "(Gel fraction of cured product)" above was cut to 25 mm x 25 mm, one of the release PET films (1-C) was peeled off, and the cured product was attached to a mirror-polished SUS substrate with a width of 25 mm, length of 100 mm, thickness of 2 mm, and a 5 mm hole at the long edge. Next, the other release PET film (1-E) was peeled off, and the mirror-polished surface of a similar SUS substrate was attached to the exposed cured product surface, and then the specimen was pressed at 215 N using a universal testing machine (A&D Co., Ltd., "Tensilon RTI-1310") and left to stand for 24 hours in an environment of 25°C to obtain a test specimen. The obtained test piece was hung from one of the SUS substrates by an S-hook, and furthermore, a weight of 1 kg was hung from the other SUS substrate. This was left at 25° C., and the time until the weight fell was measured, and the creep resistance was evaluated according to the following criteria. ○: The weight did not fall even after 48 hours. △: The time it took for the weight to fall was between 24 and 48 hours. ×: The weight took less than 24 hours to fall.
[0080] (Printability) (1) Printing method (1-1) Flexographic printing (Example 1, Comparative Example 4) The obtained photocurable resin composition was coated to a thickness of 10 μm on a PET film (Nippa Corporation, "1-E", thickness 50 μm) using a flexographic printing device (MT Tech Corporation, "Small Flexographic Printing Tester FC11"). Next, using a batch-type UV LED curing device (CSS Corporation, "UV-LED PROCESSOR LSS-61"), the composition was cured with a wavelength of 395 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm, (1-2) Screen printing (Examples 2 to 12, Comparative Examples 1 to 3, 5) The obtained photocurable resin composition was screen-printed by applying a pattern onto the inner treated surface of a PET film (Nippa Corporation, "1-E", thickness 50 μm) using a screen printer (SERIA Corporation, "SSA-PC560E"). A pattern-treated 80-mesh printing plate was used as the screen printing plate. Next, a batch-type UV LED curing device (CSS Corporation, "UV-LED PROCESSOR LSS-61") was used to apply a 395 nm wavelength, 500 mW / cm illuminance. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm, (1-3) Inkjet printing (Example 13) The obtained photocurable resin composition was applied to a PET film (Nippa Corporation, "1-E", thickness 50 μm) to a thickness of about 2 μm using an inkjet device (FUJIFILM Corporation, "Material Printer DMP-2831"), and then, using a batch-type UV LED curing device (CSS Corporation, "UV-LED PROCESSOR LSS-61"), the composition was cured with a wavelength of 395 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product was obtained by irradiating the material in such a manner that the cured product satisfies the above criteria.
[0081] (2) Evaluation of printability The resulting cured products were visually inspected and the printability was evaluated according to the following criteria. ○: When a cured product with uniform thickness and surface smoothness was obtained ×: Uneven thickness, surface irregularities or repelling
[0082] [Table 1]
[0083] [Table 2] [Industrial Applicability]
[0084] According to the present invention, it is possible to provide a photocurable resin composition having excellent adhesion and creep resistance. Also, according to the present invention, it is possible to provide a pressure-sensitive adhesive sheet using the photocurable resin composition, and a method for producing a laminate using the photocurable resin composition.
Claims
1. The composition contains a monofunctional (meth)acrylic monomer, a polyfunctional (meth)acrylic monomer, a photopolymerization initiator, and a thermoplastic resin, The thermoplastic resin has a block structure or a graft structure, The viscosity at 25°C is 0.001 Pa·s or more and 500 Pa·s or less. A photocurable resin composition comprising:
2. The photocurable resin composition according to claim 1 , wherein the thermoplastic resin comprises a thermoplastic resin having a structure derived from styrene.
3. 3. The photocurable resin composition according to claim 2, wherein the thermoplastic resin having a structure derived from styrene is a (meth)acrylic / styrene copolymer.
4. 4. The photocurable resin composition according to claim 2, wherein the content of the structure derived from styrene in the thermoplastic resin having the structure derived from styrene is 3 mass% or more.
5. 4. The photocurable resin composition according to claim 1, wherein the thermoplastic resin contains a triblock copolymer, and the content of the triblock copolymer in the thermoplastic resin is 50 mass % or more.
6. 4. The photocurable resin composition according to claim 1, wherein the thermoplastic resin has a weight average molecular weight of 100,000 or more and 500,000 or less.
7. 4. The photocurable resin composition according to claim 1, wherein the content of the thermoplastic resin in the photocurable resin composition is from 1% by mass to 60% by mass.
8. The photocurable resin composition according to claim 7 , wherein the content of the thermoplastic resin in the photocurable resin composition is from 10% by mass to 40% by mass.
9. 4. The photocurable resin composition according to claim 1, wherein the content of the polyfunctional (meth)acrylic monomer in the photocurable resin composition is from 0.3% by mass to 40% by mass.
10. The photocurable resin composition was exposed to light at a wavelength of 395 nm and an illuminance of 500 mW / cm 2 The ultraviolet light irradiation dose is 3000 mJ / cm 2 4. The photocurable resin composition according to claim 1, wherein the gel fraction of the cured product obtained by irradiating the composition so as to satisfy the above condition is from 25% by mass to 60% by mass.
11. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer comprising a cured product of the photocurable resin composition according to claim 1 .
12. The pressure-sensitive adhesive sheet according to claim 11 , comprising a substrate and a pressure-sensitive adhesive layer comprising a cured product of the photocurable resin composition on at least one surface of the substrate.
13. 4. A method for producing a laminate, comprising the steps of: printing the photocurable resin composition according to claim 1; and attaching an adherend to an object using the printed photocurable resin composition.
14. The method for producing a laminate according to claim 13, wherein the method for printing the photocurable resin composition is screen printing, inkjet printing, or flexographic printing.
Citation Information
Patent Citations
Radiation-curing adhesive composition and laminate using the same
JP2013216742A
Photocurable adhesive composition
WO2016163152A1